Maa Ledungga Expression of Social Resistance Through the Preservation of Intangible Cultural Heritage in Gorontalo Province - Dwi Anggelita Hamzah; Dian Nugroho; Mikke Susanto; Agus Rochiyardi (TUMATA: Journal of Arts and Cultural Management, 2025)
This paper examines the masterplan planning of Maa Ledungga Rice Harvest Art Festival in South Huntu Village, Bone Bolango Regency, Gorontalo. This festival is a response to modernization and land use change that threatens local agrarian traditions. Through revitalization by the Huntu Art District community, the festival functions as a harvest gratitude ritual and a space for cultural expression and strengthening of community identity. The research used literature study, participatory observation, and narrative analysis to understand the role of cultural narratives and community participation as a strategy of social resistance and culture-based creative economic development. The results show that the festival strengthens social solidarity, builds networks between farmers, artists, MSMEs and youth, and creates new economic opportunities. The festival is also a model of cultural heritage management that is relevant to contemporary needs and strengthens food security and green open spaces through the creative economy. The findings contribute to the study of culture-based creative economy and recommendations for the government and creative industry players in cultural preservation and sustainable local economic development.